Disappearance of Sherlock Holmes - Millett, Larry (Book collections on Project MUSE., 2012)
SHERLOCK HOLMES DISAPPEARS, POLICE SUSPECT FAMED DETECTIVE IN KIDNAPPING AND MURDER reads a New York headline. So begins the fifth mystery in Larry Millett's series. A letter, written in a secret cipher he recognizes all too well, reveals that an old foe of Holmes-a murderer he once captured after an incredible duel of wits-is back, has kidnapped his previous victim's widow, and is now impersonating Holmes himself. Holmes must once again match wits with a particularly cunning adversary, one whose hatred of Holmes has seemingly become the killer's single greatest obsession. Chasing the kidnappe.